The Asset Lock Under the Regular Operation of Social Enterprises in Italy - xu, ziwei (PRAWO i WIĘŹ, 2024)
Italian law establishes the legal status of social enterprises by providing the accreditation of entities that satisfy the requirements to be a social enterprise. Due to the variety of legal forms of social enterprises, the specifics of the asset lock rule may vary in the course of their regular operation. The reform of the third sector, which explicitly includes social enterprises, adds complexity to this issue. In this context, the question of how the asset lock can be used to ensure that there is no drift away from the social purpose of the social enterprise is of paramount concern. This paper will explore four main types of participants in these entities, which are directors, shareholders (or members), third parties, and the controller. To this end, the operation of the asset lock will be dissected by discussing and analyzing the constraints on directors’ remuneration, the principle of the non-distribution of profit motive, restrictions on transactions with third parties in social enterprises, and regulation by the controller during which period of operation, as well as by comparing from a theoretical point of view which of the legal forms of social enterprises would be more conducive to serving the interests of the community and the public interest.